Wound Healing Potential/Activity of Polyherbal Ointment Containing Salvadora persica, Azadirachta indica and Calendula officinalis Extracts: An Experimental Study: Wound Healing Potential: An Experimental Study (Biological Sciences - PJSIR, 2022)
The present study explore the wound healing potential of a novel herbal ointment formulation, fast wound healing ointment (FWHO) composed of 10% w/w crude ethanolic extracts of Salvadora persica (sticks), Azadirachta indica (leaves) and Calendula officinalis (whole plant) on excision wound model in albino rats. The FWHO was applied topically once daily on the wound to evaluate the rate of contraction and period of epithelialization in rats. Complete contraction and epithelialization of wound was observed at 19 day (P